The geophysical toolbox applied to forest ecosystems – A review - Loiseau, Bertille; Carrière, Simon D.; Jougnot, Damien; Singha, Kamini; Mary, Benjamin; Delpierre, Nicolas; Guérin, Roger; Martin-StPaul, Nicolas K. (The Science of the total environment, 2023)
Studying the forest subsurface is a challenge because of its heterogeneous nature and difficult access. Traditional approaches used by ecologists to characterize the subsurface have a low spatial representativity. This review article illustrates how geophysical techniques can and have been used to get new insights into forest ecology. Near-surface geophysics offers a wide range of methods to characterize the spatial and temporal variability of subsurface properties in a non-destructive and integrative way, each with its own advantages and disadvantages. These techniques can be used alone or combined to take advantage of their complementarity. Our review led us to define three topics how near-surface geophysics can support forest ecology studies: 1) detection of root systems, 2) monitoring of water quantity and dynamics, and 3) characterisation of spatial heterogeneity in subsurface properties at the stand level. The number of forest ecology studies using near-surface geophysics is increasing and this multidisciplinary approach opens new opportunities and perspectives for improving quantitative assessment of biophysical properties and exploring forest response to the environment and adaptation to climate change. [Display omitted] •Near-surface geophysical methods can efficiently address forest ecology issues.•Geophysical methods provide spatial and temporal information on soils non-intrusively.•Geophysics can help to detect and describe tree root systems.•Geophysics allows to monitor the spatial distribution and dynamics of water.•Geophysics allows characterisation of spatial heterogeneity in subsurface properties.